Peningkatan Ekonomi Masyarakat Pulau Kecil Melalui Pemanfaatan dan Pengolahan Biji Karet Dengan Teknologi Wafer Sebagai Pakan Ternak Kambing - Dewi Ananda Mucra; Triani Adelina; Anwar Efendi Harahahap; Jepri Juliantoni (MENARA RIAU, 2021)
Busuk Island is a small island located in Kuantan Singingi Regency, Riau Province. Potential resource on this island is rubber plantations. This service aims to utilize and process rubber seeds with wafer technology as goat fodder in an effort to improve community welfare. The service method is a Community Based Research (CBR) method is a method in which the community participates in this research and service process. The results show that community service activities produce 80 - 90% feedback from the community, although most people have a low level of education but it is still easy to understand the material, wafer nutrient content produced between treatments namely crude protein 10.02 - 11.40%, crude fiber 21.00 - 21.55% and crude fat 4.36 - 6.92 %. The conclusion of this service is that wafers with the addition of rubber seed waste to the level of 21% in the ration can be used as goat fodder with a community based research (CBR) service model which is an effective model to motivate farmers to increase the development and growth of goats to the maximum, so that the sale value goat livestock are also high and have implications for improving the welfare of the community